2012
DOI: 10.5194/amt-5-2469-2012
|View full text |Cite
|
Sign up to set email alerts
|

1 km fog and low stratus detection using pan-sharpened MSG SEVIRI data

Abstract: Abstract. In this paper a new technique for the detection of fog and low stratus in 1 km resolution from MSG SEVIRI data is presented. The method relies on the pan-sharpening of 3 km narrow-band channels using the 1 km high-resolution visible (HRV) channel. As solar and thermal channels had to be sharpened for the technique, a new approach based on an existing pan-sharpening method was developed using local regressions. A fog and low stratus detection scheme originally developed for 3 km SEVIRI data was used a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…re f l HRV, min_thres = re f l HRV,CS + D min (9) re f l HRV, max_thres = re f l HRV,CS + D max (10) where the re f l HRV,CS is the typical HRV reflectance in clear sky at a certain time calculated as the minimum HRV reflectance over the 10 days before at the same time of the day. This approach takes into account solar and satellite angle variations.…”
Section: Hrv Reflectance Fog Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…re f l HRV, min_thres = re f l HRV,CS + D min (9) re f l HRV, max_thres = re f l HRV,CS + D max (10) where the re f l HRV,CS is the typical HRV reflectance in clear sky at a certain time calculated as the minimum HRV reflectance over the 10 days before at the same time of the day. This approach takes into account solar and satellite angle variations.…”
Section: Hrv Reflectance Fog Testsmentioning
confidence: 99%
“…Research in satellite meteorology has shown that satellite imagery is useful for detecting fog in areas where there are no other observations. Fog detection with satellite imagery still represents a challenge and different approaches can be found in the literature [3][4][5][6][7][8][9][10][11]. A first method implemented to detect fog and low clouds was the assessment of their different reflectance characteristics compared to that of other clouds in the visible band [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many areas, METeorological Aerodrome Reports (METARs) are ideally suited to validate ground fog detection schemes (cf., e.g., Cermak and Bendix, 2011;Schulz et al, 2012). These reports are based on weather observations from airports and include cloud base heights as well as information about the visibility at ground level.…”
Section: Methodology Of Validationmentioning
confidence: 99%
“…Some are, however, required to sharpen other MODIS products needed as an input. Therefore several infrared channels are transferred to the 250 m resolution of MODIS channels 1 and 2 using a suitable pan-sharpening technique by Schulz et al (2012). According to this method a highresolution satellite channel is degraded to match the resolution of the low-resolution channel that is to be sharpened.…”
Section: Pan Sharpening Of Modis Channelsmentioning
confidence: 99%